Knowledge and Perceptions of HPV Vaccine Acceptance among African-American College Women - Lauren R. Darensbourg; Ivette A. López; Matthew T. Dutton; C. Perry Brown (University of North Florida, 2015)
Human papillomavirus (HPV) is the most prevalent sexually transmitted disease in the United States. Prevalence rates among sexually active young women are approximately 50%. An HPV vaccine has been created that has high efficacy in preventing persistent HPV infection, cervical cancer precursor lesions, and genital warts caused by four HPV subtypes. The purpose of this study was to assess African-American college women's knowledge and perceptions of HPV, and their association with the acceptance of HPV vaccination. Variable selection was guided by the Health Belief Model and the Theory of Planned Behavior. Written surveys were administered to 122 African-American women between the ages of 18 and 26 who were enrolled as undergraduates at Florida Agricultural and Mechanical University (FAMU). Statistically significant associations were found between planning to get vaccinated against HPV and several perception variables. Health education efforts aimed at African-American women in college should be renewed, given the high percentage of misconceptions about HPV among members of the study population. Interventions should appeal to social networks of the young women, as their opinions regarding the vaccine weighs in their decision to plan to get vaccinated. This study underscores the need for continuous and consistent health education interventions directed at African-American women of college age.